Impact of Kidnapping and Insecurity on the Job Perfromance of Library Staff in the University of Jos - Shittu Lukman Olayinka; Kehinde Ajao Tiamiyu; Garba Muftahu Abdullahi (Economit Journal: Scientific Journal of Accountancy, Management and Finance, 2024)
This study investigated the impact of kidnapping and insecurity on job performance of library staff in the University of Jos. The study was guided by four objectives which includes; to find out the causes of insecurity and kidnapping, to find out the impact of insecurity on job performance of library staff in University of Jos Library among others. The study also answered four research questions which includes; what are the causes of insecurity and kidnapping? What is the impact of insecurity on job performance of library staff in University of Jos Library among others. The research design employed is a quantitative descriptive survey method specifically a descriptive survey research design. The target population consists of 121 staff of the library in the permanent site University of Jos Library. A sample size of 50 staff were used for the study and the sample was selected using stratified random sampling technique for un-equal strata. The instrument used for data collection was a structured questionnaire for staff and the instrument was subjected to face and content validity. The reliability of the instrument was also established at 0.67 coefficient. The data collected was analysed simple percentage, frequency count, and mean method. The analysis revealed that, insecurity is caused by different factors such as poverty, illiteracy, social injustices among others. Also that, kidnapping and insecurity affects job performance of library staff as well as cause unproductivity and absenteeism. The study concluded that, insecurity and kidnapping are threats to job performance of library staff and all security apparatus needs to collaborate to bring and end to all security threats so as to enhance and promote job performance of library staff. The study also recommended that, there should be massive awareness and education of the people for intellectual and human resource development and also that, there should be proactive responses from the security apparatus to nap perpetrators in the board before the y unleash their evil plans among others.